STRATEGI PENGEMBANGAN TAMAN KULINER CONDONGCATUR DEPOK SLEMAN DALAM MENINGKATKAN JUMLAH KUNJUNGAN - Saputra, Arif Dwi (JURNAL MEDIA WISATA: Wahana Informasi Pariwisata, 2012)
This research aims to find out the managing, developing and promoting strategies that the management of Condongcatur Culinary Park has implemented to increase the number of visitors. The research was done using method of qualitative research. To collect data, researcher made use of methods of literature study, field survey and in-depth interview with related stokeholders. The data were analyzed in descriptive way based on SWOT analysis to evaluate the strengths and weaknessesof this culinary park from both internal and external factors so that it was easy to formulate the appropriate strategeis in managing, developing and promoting it. Based on the analysis, it is found out that all this time it has not been able to increase the number of its visitors. In fact, the analysis shows that the number has declines even more. In addition, it does not have any magnetism in terms of both culinary and non culinary aspects, which can serve as an icon to attract visitors. Key words: Magnetism, Culinary Park, Condongcatur.